Bone contusion progression from traumatic knee injury: association of rate of contusion resolution with injury severity - Pedersen DR; El-Khoury GY; Thedens DR; Saad-Eldine M; Phisitkul P; Amendola A (Dove Medical Press, 2017)
Douglas R Pedersen,1 Georges Y El-Khoury,2 Dan R Thedens,3 Mothana Saad-Eldine,1 Phinit Phisitkul,1 Annunziato Amendola4 1Department of Orthopaedics and Rehabilitation, 2Department of Radiology, University of Iowa Hospitals and Clinics, 3Department of Electrical and Computer Engineering, University of Iowa, Iowa City, IA, 4Department of Orthopaedics and Sports Medicine, Duke University Medical School, Durham, NC, USA Background: Bone contusions are frequently encountered in magnetic resonance imaging (MRI) evaluation of knee anterior cruciate ligament (ACL) injuries. Their role as indicators of injury severity remains unclear, primarily due to indeterminate levels of joint injury forces and to a lack of preinjury imaging.Purpose: The purpose of this study was to 1) quantify bone contusion pathogenesis following traumatic joint injuries using fixed imaging follow-ups, and 2) assess the feasibility of using longitudinal bone contusion volumes as an indicator of knee injury severity.Study design: Prospective sequential MRI follow-ups of a goat cohort exposed to controlled stifle trauma in vivo were compared to parallel clinical MRI follow-ups of a human ACL tear patient series.Methods: Reproducible cartilage impact damage of various energy magnitudes was applied in a survival goat model, coupled with partial resection of anterior portions of medial menisci. Both emulate injury patterns to the knee osteochondral structures commonly encountered in human ACL injury imaging as well as instability from resultant ligament laxity. Longitudinal clinical MRI sequences portrayed stifle bone contusion evolution through 6 months after the inciting event.Results: In the first 2 weeks, biological response variability dominated the whole-joint response with no apparent correlation to trauma severity. Control goats subjected to partial meniscectomy alone exhibited minimal bone response. Thereafter, 0.6 J impact bone contusions portrayed a faster rate of resolution than those induced by 1.2 J cartilage impacts.Conclusion: Bone contusion sizes combined with time of persistence are likely better measures of joint injury severity than isolated bone contusion volume. Keywords: bone contusion, contusion pathogenesis, anterior cruciate ligament, magnetic resonance imaging, knee, knee injury severity